Handgrip Strength and Nutrition Status in Hospitalized Pediatric Patients - Catarina Silva (2014)
Background: Handgrip strength (HGS) is a useful indicator of nutrition status in adults, but evidence is lacking in pediatric patients. The aim of this study was to describe the association between undernutrition and HGS in pediatric patients at hospital admission, quantifying the modifying effect of disease severity, anthropometrics, and other patient characteristics on HGS. Materials and Methods: Eighty-nine inpatients aged >= 6 years consecutively admitted were recruited in a longitudinal study. Nutrition status was evaluated using body mass index (BMI) z scores, and HGS was evaluated at admission and discharge. Results: In the total sample, 30.3% of patients were undernourished at admission, and 64% lost HGS during the hospital stay. This study showed that HGS at admission was independently associated with undernutrition defined by BMI z scores (beta = 0.256, P = .037). In this multivariate analysis, sex, age, height, and BMI z scores explained 67.1% of HGS at hospital admission. Conclusion: Lower HGS may be a potential marker of undernutrition in hospitalized pediatric patients, although HGS data should be interpreted according to sex, age, and height of the patient.